Boletus aemilii Barbier, B. permagnificus Pöder and Xerocomus truncatus Singer, Snell & Dick, in Spain - Moreno, Gabriel; Esteve Raventós, Fernando (Lazaroa, 1987)
Boletus aemilii Barbier, only known from France and ltaly and B. permagnificus Pöder, only known from Italy, are described macro and microscopically. The nomenclatural problem between Xerocomus truncatus Singer, Snell & Dick and Xerocomus porosporus Singer, Snell & Dick in Spain is discussed.